Efektywność ekonomiczna przedsiębiorstwa w aspekcie zachodzących w nim procesów inwestycyjnych - Zygmunt, Justyna (Economic Efficiency of a Company in the Aspect of its Investment Processes, 2006)
The article contains the essence of economic efficiency and the methods of its survey. It also shows the investment processes influence on financial and economic position of a company and encloses the attempt to indicate this relation in Polish companies by usage of profitability rates.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 769-775